A cross-sectional approach to regional long-run inflation in Italy - Andrea Vaona (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2007)
Considering a sample of about 70 Italian regions, this paper goes beyond the assumption that there exists a unique core inflationary process in a macroeconomy. We show that local long-run inflation rates can display remarkable variability. On the one hand they are negatively correlated with productivity growth, on the other the less competitive is the local retail sector and the higher is long-run inflation.
Keywords: R1; E31; F49; 330; purchasing power parity; long-run inflation; Balassa-Samuelson model; Kaldor-Verdoorn model